Importance of economic evaluation in health care decision making - I Aniza,; M Hossein,; R Otgonbayar,; Y Munkhtuul, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2008)
Introduction : Economic evaluations can provide “value-for money” information to those making decisions about the allocation of limited health care resources. In particular, economic evaluations can be used to identify interventions that are worth providing and those that are not. Furthermore, evaluations can be used with other approaches to help set priorities, such as program-budgeting marginal-analysis. Methodology : Compile and systematically describe from the publications, articles and reports on economic evaluation in healthcare decision making. Result : A high quality economic evaluation should provide decision makers with information that is useful, relevant, and timely. In addition, evaluations should be based on rigorous analytical methods, be balanced and impartial (credible), and be transparent and accessible to the reader. There are many situations where economic evaluations can assist decision makers: decisions by various levels of government or administrative bodies (e.g., regional health authorities, hospitals, drug plans) to fund a program, service or technology, pricing decisions by government regulators and technology manufacturers, clinical practice guidelines, priorities for research funding by governments and research-based firms, post-marketing surveillance and updates of economic information based on the use of the technology in the “real world” (which can then be used to inform one of the other types of decisions). Discussion and Conclusion : This requires that decision makers take a broad view of the impact of a technology, and decision that are more explicit and transparent. The ultimate test of an evaluation is whether it leads to better decision in the presence of uncertainty, and results in the more efficient and effective use of resources.